Firm Philanthropy in Small- and Medium-Sized Family Firms: The Effects of Family Involvement in Ownership and Management. (September 2014) - Campopiano, Giovanna; De Massis, Alfredo; Chirico, Francesco
Drawing on stewardship theory and arguments in relation to social and reputational capital, this study investigates how family involvement affects engagement in firm philanthropy in small- and medium-sized family firms. Specifically, we argue that family involvement in ownership positively influences firm philanthropy while its interaction with family involvement in management produces a negative effect. Based on a sample of 130 Italian family firms, our findings offer important implications for theory and practice and pave the way for future research in the field of philanthropy in the family firm context.